Telaah Akurasi Metode Takhrīj Hadīth Niat dan Penciptaan Manusia: Studi Komparasi Antara Al-Mu‘Jam Al-Mufahras Li Alfādh Al-Ḥadīth, Al-Maktabah Al-Shāmilah dan Jawāmi’ Al-Kalim - Kasman Kasman (Islamika Inside: Jurnal Keislaman dan Humaniora, 2022)
Takhrīj as a search for al-Ḥadīth to its original sources is the first step that must be done. There are many tools that can be used to perform takhrīj al-Ḥadīth. This paper attempts to compare the accuracy of three tools of takhrīj al-Ḥadīth that are widely used today, namely Kitab al-Mu‘jam al-Mufahras li Alfādh al-Hadts, Software al-Maktabah al-Shāmilah and Software Jawāmi‘ al-Kalim. By conducting a comparative analysis that is practiced on the takhrīj al-Ḥadīths of intention and the al-Ḥadīths of human creation, the result is that the al-Maktabah al-Shāmilah software has the highest accuracy with a 100% level both in the al-Ḥadīth of intention and of human creation, then the book al-Mu‘jam al-Mufahras li Alfādh al-Al-Ḥadīth with 100% accuracy rate for intention al-Ḥadīth and 81.82% for human creation al-Ḥadīth, and the lowest is Jawāmi‘ al-Kalim software which only reaches 50% accuracy rate for intention al-Ḥadīth and 37.5% for human creation al-Ḥadīth.